2012
DOI: 10.5402/2012/650563
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cellulolytic Bacillus subtilis Strains from Agricultural Environments

Abstract: The bioconversion of cellulose and hemicellulose to soluble sugars is important for global stabilization and a sustainable human society. Here, hundreds of cellulolytic bacteria were screened and isolated from soil, compost, and animal waste slurry in Jeju Island, South Korea. Among the isolates, three strains, SL9-9, C5-16, and S52-2, showing higher potential for practical uses were purified on carboxymethyl cellulose (CMC) agar plates and identified asBacillus subtilisstrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 27 publications
(22 reference statements)
6
52
1
1
Order By: Relevance
“…The following are This result was also similar to some studies of rice bran isolate i.e., genus Bacillus [18,25]. Most Bacillus groups had the ability to produce cellulase enzyme, such as Bacillus subtilis [26][27], Bacillus licheniformis [6],…”
Section: Molecular Identification Of Cellulolytic Bacteriasupporting
confidence: 87%
“…The following are This result was also similar to some studies of rice bran isolate i.e., genus Bacillus [18,25]. Most Bacillus groups had the ability to produce cellulase enzyme, such as Bacillus subtilis [26][27], Bacillus licheniformis [6],…”
Section: Molecular Identification Of Cellulolytic Bacteriasupporting
confidence: 87%
“…Notoriously, exoglucanase was also detected for all three strains at 24 h of incubation with maximum values at 96 and 120 h (Fig. 3A); the present activity data are similar to a previous report (Kim et al 2012). When MCC was used as the sole carbon source, endoglucanase activity increased after 48 h, reaching the maximum values at 96 and 120 h (Fig.…”
Section: Cellulolytic Activitysupporting
confidence: 80%
“…The contrasting expression levels among strains growing in CMC suggest that either eglS is not directly related to CMC degradation or that it has contrasting roles among these strains. Several authors have observed differences in cellulase activity among members of the Bacillus genus (Afzal et al 2010;Kim et al 2012). While there are no studies supporting differences in cellulase expression patterns in Bacillus, the increase in transcript levels at 24 h could have triggered the detected cellulase activities.…”
Section: Egls Expression In Bacillus Strains Grown In Cmc or MCCmentioning
confidence: 98%
“…The cell free supernatant from Bacillus subtilis strains SL9-9, C5-16, S52-2, and KACC10111 were found to bear CMCase and exoglucanase activities only. β-glucosidase activity was however present on the cell debris of the isolates studied [26]. Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Observations that members of the Bacillus genus have a complete cellulase enzyme system have been made by [26]. The cell free supernatant from Bacillus subtilis strains SL9-9, C5-16, S52-2, and KACC10111 were found to bear CMCase and exoglucanase activities only.…”
Section: Resultsmentioning
confidence: 99%